1638a Work related musculoskeletal disorders, physical work factors and psychosocial work factors for chartered physiotherapists, physical therapists and athletic therapists in ireland. (24th April 2018) - Hogan, DAM; Nolan, S; Greiner, BA
Abstract : Introduction: In the epidemiological literature, physical exposure and psychosocial work factors are now recognised as major contributing work environmental factors for work-related musculoskeletal disorders (WRMSDs). Healthcare workers such as physiotherapists and physical/athletic therapists are exposed to risk factors for WRMSDs on a daily basis, despite having specialist knowledge of body mechanics and injury prevention strategies. Methods: A cross-sectional study 'Health in Hand-Intensive Tasks and Safety' (HITS). Study sample consisted of 347 employed and self-employed practising therapists in Ireland. Postal questionnaires included questions about WRMSD symptoms, physical work risk factors, psychosocial and work organisational risk factors, among others. Analyses included logistic regression modelling. Results: 55.4% reported that they had experienced WRMSD that lasted for more than 3 days in the past 12 months. The highest physical effort perceived was repetitive thumb movements (mean=5.08) and the lowest was bending the elbows (mean=3.5). Many affected therapists classified the following physical work factors as 'majorly significant' in negatively contributing to their musculoskeletal health, the repetitiveness of work motions (54.6%) and high quantitative workload due to treating many patients/clients (49.7%). In relation to psychosocial work factors, most therapists scheduled their appointments themselves (65.7%). The odds of upper limb symptoms more than doubled (OR=2.3, 95% CI) for those not booking their appointments. Social support emerged as an important issue for both the 12 month prevalence of any upper limb symptom and the prevalence of incapacitating symptoms. The level of self-reported influence at work and predictability of work were significantly associated with incapacitating symptoms after adjustment for confounders. Conclusion: The results suggest that therapist input into scheduling of clients/patients and supervisory support may be crucial to their musculoskeletal health. For employed therapists, social support is provided from colleagues and direct supervisors, however, for self-employed therapists social support has to take other forms, through the professional bodies and other organisations.